Discriminative Long-Distance Transport of Selenate and Selenite Triggers Glutathione Oxidation in Specific Subcellular Compartments of Root and Shoot Cells in Arabidopsis - Khan, Muhammad Sayyar; Soyk, Anna; Wolf, Ingo; Peter, Miriam; Meyer, Andreas J.; Rausch, Thomas; Wirtz, Markus; Hell, Rüdiger (Frontiers in Plant Science, 2022)
Selenium is an essential trace element required for seleno-protein synthesis in many eukaryotic cells excluding higher plants. However, a substantial fraction of organically bound selenide in human nutrition is directly or indirectly derived from plants, which assimilate inorganic selenium into organic seleno-compounds. In humans selenium deficiency causes hypothyroidism and with potentially fatal consequences. Despite its importance for human health, selenium assimilation and metabolism is barely understood in plants. Here, we analyzed the impact of the two dominant forms of soil-available selenium, selenite and selenate, on plant development and selenium partitioning in plants. We found that the reference plant Arabidopsis thaliana discriminated between selenate and selenite application. In contrast to selenite, selenate was predominantly deposited in leaves. This explicit deposition of selenate caused chlorosis and impaired plant morphology, which was not observed upon selenite application. However, only selenate triggered the accumulation of the macronutrient sulfur, the sister element of selenium in the oxygen group. To understand the oxidation state-specific toxicity mechanisms for selenium in plants, we quantified the impact of selenate and selenite on the redox environment in the plastids and the cytosol in a time-resolved manner. Surprisingly, we found that selenite caused the first oxidation of the plastid-localized glutathione pool and had a marginal impact on the redox state of the cytosolic glutathione pool, specifically in roots. In contrast, selenate application caused more vigorous oxidation of the cytosolic glutathione pool but also impaired the plastidic redox environment. In agreement with the predominant deposition in leaves, the selenate-induced oxidation of both glutathione pools was more pronounced in leaves than in roots. The consequences of these findings for tissue-specific selenium toxicity in plants will be discussed.